Immune Activation, Immunosenescence, and Osteoprotegerin as Markers of Endothelial Dysfunction in Subclinical HIV-Associated Atherosclerosis - Alessandra D’Abramo; Maria Antonella Zingaropoli; Alessandra Oliva; Claudia D’Agostino; Samir Al Moghazi; Giulia De Luca; Marco Iannetta; Claudio Maria Mastroianni; Vincenzo Vullo (Mediators of Inflammation)
HIV-infected patients have a significantly greater risk of cardiovascular disease. Several markers including osteoprotegerin have been shown to be involved in the development and progression of atherosclerosis. We investigated the relationship between T-cell phenotype, osteoprotegerin, and atherosclerosis evaluated by carotid intima-media thickness (c-IMT) in 94 HIV+ patients on suppressive antiretroviral therapy with Framingham score <10%. As for the control group, 24 HIV-negative subjects were enrolled. c-IMT was assessed by ultrasound. CD4+/CD8+ T-cell activation (CD38+ HLADR+) and senescence (CD57+ CD28−) were measured by flow cytometry. IL-6 and OPG levels were measured by ELISA kit. c-IMT was higher in HIV+ than in controls. Among HIV+ patients, 44.7% had pathological c-IMT (≥0.9 mm). CD8+ T-cell activation and senescence and OPG plasma levels were higher in HIV+ patients than in controls. Subjects with pathological c-IMT exhibited higher CD8+ immune activation and immunosenescence and OPG levels than subjects with normal c-IMT. Multivariate analysis showed that age, CD8+ CD38+ HLADR+, and CD8+ CD28− CD57+ were independently associated with pathological c-IMT. Several factors have been implicated in the pathogenesis of atherosclerosis in HIV patients. Immune activation and immunosenescence of CD8+ T cell together with OPG plasma levels might be associated with the development and progression of early atherosclerosis, even in the case of viral suppression.